Numerical and experimental investigation of thermo-fluid flow and element transport in electromagnetic stirring enhanced wire feed laser beam welding. (December 2019) - Meng, Xiangmeng; Artinov, Antoni; Bachmann, Marcel; Rethmeier, Michael
Highlights: The transport phenomena of electromagnetic stirring enhanced WFLBW is studied using a novel model. The electromagnetic stirring increases the melt flow velocity at the rear and lower regions of molten pool. The keyhole collapses more frequently at the upper part under the stirring action. The added element from filler wire is homogenized due to the enhanced forward and downward flow. Abstract: The introduction of electromagnetic stirring to laser beam welding can bring several beneficial effects e.g. element homogenization and grain refinement. However, the underlying physics has not been fully explored due to the absence of quantitative data of heat and mass transfer in the molten pool. In this paper, the influence of electromagnetic stirring on the thermo-fluid flow and element transport in the wire feed laser beam welding is studied numerically and experimentally. A three-dimensional transient heat transfer and fluid flow model coupled with dynamic keyhole, magnetic induction and element transport is developed for the first time. The results suggest that the Lorentz force produced by an oscillating magnetic field and its induced eddy current shows an important influence on the thermo-fluid flow and the keyhole stability. The melt flow velocity is increased by the electromagnetic stirring at the rear and lower regions of molten pool. The keyhole collapses more frequently at the upper part. The additional elements from the filler wire are significantly homogenized because of the enhanced forward and downward flow. The model is well verified by fusion line shape, high-speed images of molten pool and measured element distribution. This work provides a deeper understanding of the transport phenomena in the laser beam welding with magnetic field.